2014
DOI: 10.1007/978-3-319-05879-5_1
|View full text |Cite
|
Sign up to set email alerts
|

The Organization of the Sphingosine 1-Phosphate Signaling System

Abstract: The understanding of the role of the sphingosine 1-phosphate signaling system in immunology and host defense has deepened exponentially over the past 12 years since the discovery that lymphocyte egress was reversibly modulated by sphingosine 1-phosphate receptors, and with the development of fingolimod, a prodrug of a nonselective S1P receptor agonist, for therapeutic use in the treatment of relapsing, remitting multiple sclerosis. Innovative genetic and chemical approaches, together with structural biology, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 113 publications
1
22
0
Order By: Relevance
“…We demonstrated that S1P specifically interacts with (binds to) N-terminal domain of HSP90α. A specific binding site(s) of S1P to S1P receptors have been largely characterized (26). However, likewise TRAF2 and cIAP2, a specific interaction (binding) site(s) of S1P to HSP90s remains unknown.…”
Section: Identification Of Heat Shock Proteins In the S1p-mediated Simentioning
confidence: 99%
“…We demonstrated that S1P specifically interacts with (binds to) N-terminal domain of HSP90α. A specific binding site(s) of S1P to S1P receptors have been largely characterized (26). However, likewise TRAF2 and cIAP2, a specific interaction (binding) site(s) of S1P to HSP90s remains unknown.…”
Section: Identification Of Heat Shock Proteins In the S1p-mediated Simentioning
confidence: 99%
“…SK1 has well-described functions in cell signalling, such as TNF-a-stimulated NFk B activation (Alvarez et al, 2010;Leclercq & Pitson, 2006;Maceyka et al, 2009;Xia et al, 2002), and in cell death/survival decisions (Pitson, 2011). The product of SK activity, S1P, can have intracellular signalling functions or be secreted from cells to act on cell surface S1P receptors (Leclercq & Pitson, 2006;Rosen et al, 2014;Spiegel & Milstien, 2011;Xia & Wadham, 2011). A number of studies have shown that modulating the S1P/receptor can reduce virus-induced disease and tissue injury associated with IAV (Marsolais et al, 2009;Walsh et al, 2011) and in an animal model of RSV infection (Walsh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sphingosine-1-phosphate (S1P) is a bioactive lipid which has been shown to exert important biological functions in a variety of systems such as the immune and cardiovascular systems as well as in the regulation of cancer cells [ 1 - 4 ]. S1P can function as a primary messenger to act on a family of five G-protein-coupled receptors (S1P receptors, S1PR 1–5 ) (reviewed by [ 5 , 6 ]). Several recent studies also demonstrate that S1P is involved in the sensation and modulation of pain (reviewed by [ 7 , 8 ]).…”
Section: Introductionmentioning
confidence: 99%